Frontispiece: A Compound I Mimic Reveals the Transient Active Species of a Cytochrome P450 Enzyme: Insight into the Stereoselectivity of P450‐Catalysed Oxidations. Issue 13 (13th March 2023) - Suzuki, Kazuto; Stanfield, Joshua Kyle; Omura, Keita; Shisaka, Yuma; Ariyasu, Shinya; Kasai, Chie; Aiba, Yuichiro; Sugimoto, Hiroshi; Shoji, Osami
Abstract : Enzymes . In their Research Article (e202215706 ), Hiroshi Sugimoto, Osami Shoji et al. report the crystal structure of cytochrome P450BM3 mimicking the state of the enzyme in the moment preceding epoxidation.